Combined Influences of Dementia Exposure and Personality on Self-Reported Memory Problems. (7th February 2020) - Mogle, Jacqueline; Hill, Nikki L.; Bell, Tyler Reed; Bhargava, Sakshi; Bratlee-Whitaker, Emily; Wion, Rachel K.; Tiwari, Pooja Anushka
The current study investigated whether having a first-degree relative with dementia influenced older adults' self-reported memory, if personality traits moderated these associations, and whether these associations differed by the type of item asked (ie, frequency of memory problems vs perceived memory decline). Data drawn from the Einstein Aging study included 454 older adults ( M age = 76.64, standard deviation = 4.77, 66.96% white, and 63% female). Multilevel modeling analyses showed participants who had a first-degree relative with dementia reported more frequent memory problems and were more likely to report memory decline over the past year. Among participants with a first-degree relative with dementia, higher levels of neuroticism were related to reports of more frequent memory problems at baseline, whereas higher levels of conscientiousness and lower levels of extraversion were related to reports of more frequent memory problems over time. Future research should consider personality traits and family history of dementia as potential contributors to self-reported memory problems.